(untitled) (International Journal of Engineering and Computer Science, 2017)
The purpose of this paper is to present designing and simulation of circular microstrip patch antenna. The return loss, gain and radiation pattern are analyzed and optimization is performed by making dual stacked circular microstrip patch antenna.FR4 is used for designing purpose which is easily available and having low cost. it is able to achieve a return loss of -41.9637dB for dual stacked microstrip antenna from -23.0774dB for simple circular microstrip patch antenna.The increase in gain of 4 dB occur.